ASSOCIATION BETWEEN BODY MASS INDEX AND DEMIRJIAN-BASED DENTAL AGE ESTIMATION IN CHILDREN: EVIDENCE FROM PANORAMIC RADIOGRAPHS - Swastirani, Astika; Pratama, Liki Arkhan; Rahmayati, Nabilah Shafiyyah; Kurniawati, Sari (FKG ULM, 2026)
Background: Age estimation is a crucial aspect of forensic dentistry, particularly in identifying children whose chronological age is uncertain or undocumented. The Demirjian method is one of the most widely used approaches to determine age by evaluating the mineralization stages of seven mandibular permanent teeth using panoramic radiographs. Body Mass Index (BMI) reflects nutritional status and general growth patterns, which may influence the rate of dental maturation. Purpose: This study aimed to analyze the correlation between BMI and dental age estimation based on the Demirjian method in children. Methods: This analytical observational study with a cross-sectional design involved 42 children who underwent panoramic radiographic. BMI values were calculated from measurements of body weight and height, while dental age was determined by assessing tooth development stages using the Demirjian method. Results: The results of the Spearman test showed that 90.4% of participants had consistent dental and chronological ages, 4.8% showed advanced, and 4.8% delayed dental maturation. Significant correlation was found between BMI and dental age (p= 0.038), while a not-significant correlation was observed between BMI and chronological age (p= 0.117). There was a significant correlation between dental age and chronological age (p= 0.000). The intraclass correlation coefficient (ICC= 0.997) indicated excellent inter-examiner reliability. Conclusion: These findings suggest that BMI variation is associated with differences in dental development, indicating its potential use as a complementary indicator in biological age estimation within forensic dentistry; however, this association should be interpreted cautiously, as potential confounding factors were not controlled in this study.Keywords: Body Mass Index, Dental Age, Demirjian Method, Panoramic Radiography, Children